2020
DOI: 10.1186/s13068-020-01789-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptome and proteome analyses provide new insights into different stages of Akebia trifoliata fruit cracking during ripening

Abstract: Background: Akebia trifoliata (Thunb.) Koidz may have applications as a new potential source of biofuels owing to its high seed count, seed oil content, and in-field yields. However, the pericarp of A. trifoliata cracks longitudinally during fruit ripening, which increases the incidence of pests and diseases and can lead to fruit decay and deterioration, resulting in significant losses in yield. Few studies have evaluated the mechanisms underlying A. trifoliata fruit cracking. Results: In this study, by observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…Fruit ripening leads to the development of soft and edible fruit, which is one of the most important changes that determine fruit quality and improve palatability ( 25 ). However, only two recent study has reported the use of transcriptome sequencing for A. trifoliata fruit ( 14 , 17 ), and the limited genetic research has impeded an understanding of the genetic basis for its postharvest quality control, consumer acceptance, and breeding for cultivar improvement. Proteomic-based technologies have been extensively applied to analyze many aspects of fruit development; large-scale protein profiling and proteomic analysis provide more direct information on fruit softening at the protein level ( 9 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fruit ripening leads to the development of soft and edible fruit, which is one of the most important changes that determine fruit quality and improve palatability ( 25 ). However, only two recent study has reported the use of transcriptome sequencing for A. trifoliata fruit ( 14 , 17 ), and the limited genetic research has impeded an understanding of the genetic basis for its postharvest quality control, consumer acceptance, and breeding for cultivar improvement. Proteomic-based technologies have been extensively applied to analyze many aspects of fruit development; large-scale protein profiling and proteomic analysis provide more direct information on fruit softening at the protein level ( 9 , 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…8” fruit at different development stages (UR, HR, and FR) were analyzed using RT-qPCR to evaluate the expression profiles of selected DAPs. Total RNA was extracted according to the method previously described by Niu et al ( 14 ), and the cDNA synthesis was performed with the Hiscript qRT SuperMix (Vazyme, Biotech). The primers of an internal control gene ( EF- α) and candidate genes were designed with Primer 5.0 ( Supplementary Table 1 ), and the reaction was carried out using SYBR Green PCR master mix (Aidlab Biotechnologies, Co., Ltd) in a Bio-Rad CFX96 PCR system (Bio-Rad, Richmond, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations